The mystery off Glen Road - Campbell, Julie, 1908-1999.; Stevens, Mary (New York : Random House, 2004)
After a storm blows through Sleepyside and damages the Bob-Whites' clubhouse, Trixie and Honey take a job patrolling the game preserve and find evidence of a poacher.
Originally published: Trixie Belden and the mystery off Glen Road. New York : Golden Books, 1956.
Keywords: Clubs -- Fiction; Poaching -- Fiction; Mystery and detective stories